Respuesta :
Equation of the line: (y - 3) = -2/3 (x - 4)
Compare it with: (y - y1) = m(x - x1)
Then, m = -2/3
Now, we know perpendicular line must have equal & opposite slope so:
It would be: 3/2
In short, Your Answer would be 3/2
[ Please check the options ]
Hope this helps!
Compare it with: (y - y1) = m(x - x1)
Then, m = -2/3
Now, we know perpendicular line must have equal & opposite slope so:
It would be: 3/2
In short, Your Answer would be 3/2
[ Please check the options ]
Hope this helps!
Answer:
[tex]\frac{3}{2}[/tex] will be the slope of the line perpendicular to xy.
Step-by-step explanation:
The equation of line xy is ( y-3 ) = [tex]\frac{-2}{3}[/tex] (x-4)
y = [tex]\frac{-2}{3}[/tex] ( x-4 ) + 3
y = [tex]\frac{-2}{3}[/tex] x + [tex]\frac{8}{3}[/tex] + 3
y = [tex]\frac{-2}{3}[/tex] x + [tex]\frac{17}{3}[/tex]
So the line has slope = [tex]\frac{-2}{3}[/tex] and y-intercept = [tex]\frac{17}{3}[/tex].
Let m is the slope of a line perpendicular to line xy.
We know that for perpendicular lines having slopes m₁ and m₂
m₁ × m₂ = -1
Therefore, for m₁ = m and m₂ = [tex]\frac{-2}{3}[/tex]
mx ([tex]\frac{-2}{3}[/tex]) = -1
m = ([tex]\frac{3}{2}[/tex])
[tex]\frac{3}{2}[/tex] will be the slope of the line perpendicular to xy.